(Developments and Innovation of Food technology to Produce of Health Food Products andIts Market Prospect) - Agus Sudibyo (Warta Industri Hasil Pertanian, 2009)
In recently years, the increase cause of the illness related life style, such as diabetes mellitus and obesity, cardiovascular and cancer diseases, have been characterized as social issues which leads to the loss of quality of life and increases in medical care expenses. On the other hand, to make a guarantee to extend the length of a healthy life expecting in an aging society is society is significant social issue in the world. Consequently, modern nutritional science was needed to provide ever more information on the functions and mechanisms of specific food components in health promotion and/or diseases prevention. Recent innovations in food technologies have led to the use of many traditional technologies, such as fermentation, extraction, encapsulation, fat replacement, and enzyme technology, to produce new health food ingredients, reduce or remove undesirable food components, add specific nutrient or functional ingredients, modify food compositions, mask undesirable flavors or stabilize ingredients.Modern biotechnology has also changed fundamentally the way foods are created; meanwhile nanotechnology is also beginning to find potential applications in the area of food and agriculture. In the global marketplace food products for health, especially functional food and netraceuticals have a multi-billion dollar industry and development of food product for health with distinctive genetic and ecotype traits has to deliver unique product to the world was large quantity. this paper offers a brief overview of the developments and annovations of the food product for health with technologies involved in ingredient modification, protecting ingredient and controlling delivery. Furthermore, it discusses the prospect of these food product currently in the market.